Strategies for the Promotion of Primary Health Care Research in Portugal: A Qualitative Study - Morgado, Maria Beatriz (2023)
Introduction: There are several barriers discouraging clinicians from undertaking research, including insufficient funding, lack of time, organizational issues and lack of support. The strengthening of research capacity is perceived from three levels: characteristics of the researcher, the environment, and organizational issues. To date, Portugal is lacking studies on this subject. The aim of this study was to identify the best practices to promote research in Portuguese Primary Health Care.Methods: We conducted a qualitative study using semi-structured interviews with family doctors with broadly recognized research work and other stakeholders. We selected a sample by convenience and snowball sampling. From a total of 14 doctors invited by email, 12 responded positively, and we subsequently included two other stakeholders. We conducted the interviews in digital or face-to-face formats. Two team members handled the coding of interviews independently. We kept all recordings and transcripts confidential, only accessible to researchers.Results: We identified 16 strategies: 1) increasing institutional support; 2) creating support structures; 3) redefining the residency program; 4) investing in research training; 5) redefining curriculum evaluation; 6) establishing dedicated time for research; 7) increasing funding; 8) improving access to research data; 9) being a research driver; 10) establishing a research culture; 11) working in collaboration; 12) creating formally organized research groups; 13) creating autonomous research centers; 14) improving the definition of the research subjects and study designs; 15) reviewing procedures for ethics’ committees; and 16) reviewing the current selection of articles for publication.Conclusion: Overall, a greater proportion of interviewees identified the following as the most relevant strategies for research promotion: institutional support, including technical and scientific support from public institutions, private entities and academic centers; the reorganization of working hours with protected time for research; increased funding directed towards research and breaking isolation in research, promoting teamwork with clinicians within the same area or from different professional backgrounds.